PEMBAGIAN HARTA WARISAN PADA MASYARAKAT ADAT DAYAK PAKPAK OLEH TEMENGGUNG ADAT MENURUT HUKUM ADAT DAYAK PAPAK DI DESA NANGA UNGAI KECAMATAN KAYAN HULU - Tri Minarti (Universitas Kapuas Sintang, 2021)
Dayak Pakpak tribe is one of the Dayak tribes in Sintang regency, it is located at Nanga Ungai village, Kayan Hulu Subdistrict, whereas at there the distribution of inheritance uses a customary law until nowadays.The research discussion designed toward the performance distribution of inheritance on Dayak Pakpak community by the Temenggung adat which related to the Customary Law of Dayak Papak in Nanga Ungai Village, Kayan Hulu subdistrict.The approach used in this research is a Sociological Juridical Method. The approach is defined as problem analysis through legal research of factual facts in institution concerned or toward the community which covered as problems handled in the research.As results, the implementation of inheritance distribution on Dayak Pakpak community by the Temenggung adat are suitable with a customary law of Dayak Papak in Nanga Ungai Village, Kayan Hulu subdistrict, which is implementedby Temenggung with the beneficiary in accordance with the beneficiary’s orders for the period of his lifetime, as for the group who gets the inheritance biological child, wife/husband, parents (father/mother:only if the person concerned dies), grandchildren (in case the child is no longer there) and grand children (in case the grandchild is not there).In conclusion, according to the customary law of Dayak Papak in Nanga Ungai Village, Kayan Hulu District, it is carried out by Temenggung together with the heirs in accordance with the heir’s orders during his lifetime. The group who gets the inheritance Natural children, wife / husband, parents (father / mother if the person concerned dies), grandchildren (in this case the child is no longer there) and grandchildren (in this case the grandchild is not there). Then after, if there is a debate in those family mentioned in receiving the assets, it should be resolved by gathering together as means of talk for finding solution and the Head of Custom together with the Temenggung must be engaged.